2019
DOI: 10.1017/s1366728918001190
|View full text |Cite
|
Sign up to set email alerts
|

Assessing bilingual language switching behavior with Ecological Momentary Assessment

Abstract: The putative bilingual executive advantage has been argued to stem from lifelong experience with executively demanding language behaviors, such as switching between the two languages. However, studies testing for possible associations between language switching frequency and EF in bilinguals have yielded inconsistent results. One reason for this could lie in the methods used that have evaluated the frequency and type of language switches with retrospective self-reports, as well as in problems in reliability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…It could be argued that the finding in our previous EMA study (Jylkkä et al, 2019) where contextual switches were associated with better executive performance was because the EMA question concerning contextual switches tapped on switching in a Dual language context. In our contextual switches question "How large proportion of the aforementioned language switches took place in situations in which you typically always switch between languages?…”
Section: Everyday Language Switching and Efmentioning
confidence: 77%
See 1 more Smart Citation
“…It could be argued that the finding in our previous EMA study (Jylkkä et al, 2019) where contextual switches were associated with better executive performance was because the EMA question concerning contextual switches tapped on switching in a Dual language context. In our contextual switches question "How large proportion of the aforementioned language switches took place in situations in which you typically always switch between languages?…”
Section: Everyday Language Switching and Efmentioning
confidence: 77%
“…(Verreyt et al, 2016;see also Johnson et al, 2015;Prior & Gollan, 2011). In an earlier experiment (Jylkkä, Soveri, Laine, & Lehtonen, 2019), we addressed this problem by utilizing Ecological Momentary Assessment (EMA), where the language switches made by a speaker were probed multiple times a day using a smartphone application. The results indicated that the retrospective language switching questionnaires and individual questions are not valid.…”
Section: Everyday Language Switching and Efmentioning
confidence: 99%
“…Alternatively, the reliability and validity issues related to the retrospective measurement of LS behavior could be overcome by using more ecological measures. For instance, Jylkkä et al (2019) assessed LS using the Ecological Momentary Assessment (EMA), in which participants were asked to report their intended, unintended, and contextual LS (by answering one question for each type of LS) every two-hours during 14 days. Although it could be interesting to include items asking for the directionality of the switch (i.e., L1S and L2S), the assessment of LS with EMA emerges as a promising instrument with the potential of improving those single and multiple-item retrospective scales previously used in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, several studies have previously set its scope on the interplay between executive control and self-reported natural LS behavior. In particular, the aforementioned research has investigated how the individual differences in bilinguals' natural LS are associated with the inhibition of distracting information (Jylkkä et al, 2019(Jylkkä et al, , 2017Rodriguez-Fornells et al, 2012;Soveri et al, 2011;Verreyt et al, 2016), response suppression (Rodriguez-Fornells et al, 2012), working memory updating (Jylkkä et al, 2019(Jylkkä et al, , 2017, and task-switching (Jylkkä et al, 2019(Jylkkä et al, , 2017Prior & Gollan, 2011;Soveri et al, 2011), with varying samples, tasks, and results, that depict a blurred picture of the phenomenon. Thereby, associations between different kinds of LS and executive control measures seem inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have used self-report measures to assess language switching behaviour in daily life. However a recent study (Jylkkä, Soveri, Laine & Lehtonen, 2019) has shown that these types of measures lack validity and do not represent a reliable estimate of language switching. In our study, participants provided a self-estimated switching frequency right after completing the voluntary naming task.…”
Section: Introductionmentioning
confidence: 99%